Calculating the magnetocaloric effect in second-order-type material by micromagnetic simulations: A case study on Co2B. (1st March 2020) - Ohmer, Dominik; Yi, Min; Fries, Maximilian; Gutfleisch, Oliver; Xu, Bai-Xiang
Graphical abstract: Abstract: We propose a calculation scheme which integrates micromagnetic simulations and the Arrott–Noakes equation for the investigation of the influence of microstructure and magnetocrystalline anisotropy on the magnetocaloric effect (MCE) in second-order magnetic phase transition materials. Using the Arrott–Noakes equation, the micromagnetic simulation results are extrapolated to temperatures above Curie temperature and applied to MCE calculations. With Co2 B as model material, we found that increasing magnetocrystalline anisotropy facilitates higher isothermal entropy changes ( Δ S T ). The grain size reduction results in increased Δ S T for constant saturation magnetization ( M S ), while Δ S T decreases for a reduction of M S with reduced grain size.